2002
DOI: 10.1021/la0262506
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers Supported on TiO2:  Comparison of C18H37SiX3 (X = H, Cl, OCH3), C18H37Si(CH3)2Cl, and C18H37PO(OH)2

Abstract: The solution-phase reactions of octadecylsilanes with different headgroups (C18H37SiH3, C18H37Si(OCH3)3, C18H37SiCl3, and C18H37Si(CH3)2Cl) and of octadecylphosphonic acid (C18H37PO3H2) with titanium dioxide (anatase) were investigated. Chemical analysis and FTIR suggested that all the reactions, with the exception of that of C18H37Si(CH3)2Cl, yielded closely packed self-assembled monolayers (SAMs). SAMs were characterized with high grafting density (∼4.3-4.8 octadecyl groups/nm 2 ) and with high degree of ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
180
3
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(204 citation statements)
references
References 48 publications
14
180
3
7
Order By: Relevance
“…nm -2 for closely packed monolayers of APAs, which has been estimated by the cross-section area of the phosphonic acid head group (σ = 0.23 nm 2 ) [17] . This result also agrees with experimental surface coverages reported in the literature for ODPA on mica [18] , TiO 2 [19] , ZrO 2 [19] and Si/SiO 2 [20] . In the tridentate models we had to remove a proton from the adjacent adsorption site for each APA molecule in order to balance the positive charge which is implicated in this coordination mode (see Figure 2d) [10] .…”
Section: Computational Detailssupporting
confidence: 92%
“…nm -2 for closely packed monolayers of APAs, which has been estimated by the cross-section area of the phosphonic acid head group (σ = 0.23 nm 2 ) [17] . This result also agrees with experimental surface coverages reported in the literature for ODPA on mica [18] , TiO 2 [19] , ZrO 2 [19] and Si/SiO 2 [20] . In the tridentate models we had to remove a proton from the adjacent adsorption site for each APA molecule in order to balance the positive charge which is implicated in this coordination mode (see Figure 2d) [10] .…”
Section: Computational Detailssupporting
confidence: 92%
“…The asymmetric and symmetric stretch of -CH 2 groups characteristic of a chloropropyl agent are visible in the TiSA and TiAT spectra at 2961 and 2935cm -1 , respectively. 18 Other modes at 1338, 1386, and 1471 cm -1 can be attributed to the deformation mode δ(CH 2 ) of the propyl bridging group. 19 The small absorption band observed at 2858 cm -1 is due to the -CH stretching of aromatic olefins, confirming the anchorage of the 2-aminothiazole group.…”
Section: Resultsmentioning
confidence: 99%
“…These represent the best grafted layer. Different studies with octadecylphosphonic acid (OPDA) [176][177][178] on metal oxide supports showed the formation of well-ordered monolayers with high grafting densities of about 4 groups/nm -2 . Self-assembly monolayers, comprising the molecules of three phosphonic acids, namely CF 3 (CF 2 ) 7 (CH 2 ) 11 PO 3 H 2 , n-C 16 H 33 PO 3 H 2 and n-C 22 H 45 PO 3 H 2 , on the surface of aluminium metal covered with a native oxide film were studied [179].…”
Section: Phosphorous Coupling Agents As Surface Modifiersmentioning
confidence: 99%